2016
DOI: 10.1371/journal.pone.0168985
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Genomic Study of the Novel Bacteriophage HY01 Infecting Both Escherichia coli O157:H7 and Shigella flexneri: Potential as a Biocontrol Agent in Food

Abstract: BackgroundEscherichia coli O157:H7 and Shigella flexneri are well-known food-borne pathogens causing severe food poisoning at low infectious doses. Bacteriophages have been approved for food applications by the US Food and Drug Administration (FDA) and have been suggested as natural food preservatives to control specific food-borne pathogens. To develop a novel natural food preservative against E. coli O157:H7 and S. flexneri, a new bacteriophage needs to be isolated and characterized.Methodology/Principal Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 33 publications
4
57
1
Order By: Relevance
“…Lee et al ( 2016 ) suggested that besides bacteriophage cocktails, a solution for simultaneous biocontrol of several foodborne pathogens could be the cloning of several receptor binding genes into a single bacteriophage. For either purpose, obtaining knowledge about new bacteriophages capable of infecting these pathogens and assessing their host spectrum is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al ( 2016 ) suggested that besides bacteriophage cocktails, a solution for simultaneous biocontrol of several foodborne pathogens could be the cloning of several receptor binding genes into a single bacteriophage. For either purpose, obtaining knowledge about new bacteriophages capable of infecting these pathogens and assessing their host spectrum is essential.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth mentioning that the truncation of ORF1 annotated as "tail fibers" in P206 (ORF5 in C203) seems to have no effect on the host specificity of the phage when compared to C203. Lee et al (2016) have proposed that genes associated with host specificity should be cloned into one bacteriophage genome, which then could be used as a universal agent against several related pathogenic bacteria. Broad host spectrum bacteriophages such as C203/P206 could be a potential source of such host specificity associated genes, or alternatively, it could be used in its native form as biocontrol agent either as a stand-alone or in phage cocktails.…”
Section: Discussionmentioning
confidence: 99%
“…One step growth experiment to determine burst size was performed on E. coli MG1655 according the protocol of Lee et al, (2016) with some modifications. Briefly, 2x10 8 bacteria were mixed with 2x10 6 phages, setting multiplicity of infection (MOI) to 0.01 in Luria-Bertani broth (LB), and incubated for 20 minutes at room temperature.…”
Section: One Step Growth Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a new lytic phage vB_ShiP-A7 was isolated and characterized, with lytic activity against both MDR S. exneri clinical strain and several MDR E. coli clinical strains (Table 1). Several phages were reported to have the ability to infect both E. coli and Shigella [40,41,42]. Since E. coli and Shigella are genetically similar, it is reasonable to expect some similar phages would target both strains.…”
Section: Discussionmentioning
confidence: 99%